Public awareness of palliative care in Sweden. Issue 4 (June 2018) - Westerlund, Caroline; Tishelman, Carol; Benkel, Inger; Fürst, Carl Johan; Molander, Ulla; Rasmussen, Birgit H.; Sauter, Sylvia; Lindqvist, Olav
Objective: The aim of this study was to investigate the awareness of palliative care (PC) in a general Swedish population. Design: We developed an e-survey based on a similar study conducted in Northern Ireland, consisting of 10 questions. Closed questions were primarily analyzed using descriptive statistics. Open questions were subject to inductive qualitative analysis. Subjects: The study utilized a population sample of 7684 persons aged 18–66, of which 2020 responded, stratified by gender, age and region. Results: Most participants reported 'no' ( n = 827, 41%) or 'some' ( n = 863, 43%) awareness of PC. Being female or older were associated with higher levels of awareness, as was a university-level education, working in a healthcare setting and having a friend or family member receiving PC. Most common sources of knowledge were the media, close friends and relatives receiving PC, as well as working in a healthcare setting. Aims of PC were most frequently identified as 'care before death', 'pain relief', 'dignity' and a 'peaceful death'. The preferred place of care and death was one's own home. The main barriers to raising awareness about PC were fear, shame and taboo, along with perceived lack of information and/or personal relevance. The term 'palliative care' was said to be unfamiliar by many. A number of strategies to enhance awareness and access to PC were suggested, largely reflecting the previously identified barriers. Conclusions: This survey found limited awareness of palliative care in an adult sample of the Swedish general public ≤ 66 years, and points to a more widespread disempowerment surrounding end-of-life issues.